Automatic Extraction of Interior Orientation Data in Aerial Photography Using Image Matching Method - Wijaya, Helmy Mukti; Hariyanto, Teguh; Handayani, Hapsari (Institut Teknologi Sepuluh Nopember, 2020)
The Interior Orientation is a set of parameters that have been determined to transform the coordinates of the camera photo. The pixel coordinates of Fiducial Mark in the base image (Search window) are obtained automatically. The template of the fiducial mark is designed on single-frame aerial photographs. The concept of photogrammetry with Image Matching techniques is applied in the programming works. The Normalized Cross-Correlation (NCC) method coupling with the Area Based Matching technique is precisely used in the automatic computation for measuring the coordinate of fiducial marks. Herein, three templates are provided for this calculation. The coordinates from the manual rectification are employed. The results reveal that the third template is more accurate than the others with the RMSE value of 0.0066. The accuracy regarding the results of manual rectification depends on the operator when they are identifying for pixel values.